Diagenesis and Its Impact on the Reservoir Quality of Continental Shales: A Case Study of the Lower Jurassic Da'anzhai Member of the Ziliujing Formation in the Sichuan Basin, China. (22nd February 2022) - Zhu, Yixiu; Li, Zezhou; Zeng, Lianbo; Liu, Zhenyu; Wang, Xinyao
Abstract : The Jurassic continental shale oil (gas) is a favorable unconventional resource in the Sichuan Basin of China. In this paper, analysis methods such as core and outcrops observation, thin section identification, scanning electron microscopy (SEM), and X-ray diffraction (XRD) are used to describe the characteristics of lacustrine fine-grained rock reservoir in Da'anzhai Member of the Ziliujing Formation in Sichuan Basin, and it discussed the influence and control of lacustrine fine-grained rock diagenesis on the quality of the reservoir, in order to determine the shale reservoir control factors. The results show that there are three types of rocks in the Da'anzhai Member, which are mudstone, siltstone, and limestone, and the rock combination of shell shale intercalated with shell limestone is developed in the Da 2 submember. Fine-grained sedimentary rocks in this section have undergone compaction, cementation, dissolution, metasomatism, transformation of clay minerals, and hydrocarbon generation of organic matter, which are currently in the middle diagenetic stage A or B substage. Compaction and cementation are the main factors that control the physical use of shale and limestone, and strong cementation is the main reason for the tightness of limestone reservoirs in the Da'anzhai Member in the northern and eastern parts of Sichuan Basin. The difference between dissolution and cementation is the main control factor for the formation of limestone or argillaceous limestone reservoirs in the same section in central Sichuan Basin. The organic-rich shale and shell shale of the Yuanba and Fuling area are the most favorable reservoirs of the Ziliujing Formation in this region. The shell limestone that experienced favorable dissolution in the Da'anzhai Member in the central of the Sichuan Basin has become a limestone reservoir. Discussing the impact of continental fine-grained rock diagenesis on the reservoir can better explore and develop similar intervals, enrich unconventional shale oil and gas accumulation and storage theories, and provide basic theoretical support for finding favorable unconventional shale oil and gas reservoirs.